Schizophrenia and the nurse's role in treatment adherence: An integrative review (Research, Society and Development, 2021)
Objective: to evaluate the role of nurses in the care provided to users in health services diagnosed with schizophrenia. Method: This is an exploratory research with a qualitative approach carried out through a review of national and international scientific articles, in the Virtual Health Library (VHL) databases, Scielo and in the literature in the area that address the problem selected for this study. Results: 15 studies published between 2014-2021 were included, later divided into two categories. Final considerations: It is clear that the lack of interest of professionals in this issue is of great relevance and those who allow themselves to act do not have technical support, empowerment and continuous improvement in health institutions that develop their work, it is noted that the role of the nurse It is essential in the care of schizophrenic patients, as it is directed either at the identification of signs and symptoms or at the assessment of the individual's needs, making together with the interdisciplinary team the Singular Therapeutic Plan (PTS) always focusing on the particularity of each case, aiming at the best quality of life.